Unit costs for allopathic and AYUSH outpatient care in public facilities in Urban Delhi, India - Charu C. Garg; Roopali Goyanka (Journal of Family Medicine and Primary Care)
Introduction: The National Health Policy, 2017, suggests pluralism in health care with the integrated delivery of AYUSH and allopathic care at public facilities. Information on unit cost of outpatient visits for both types of care at public facilities is useful to guide the policies on health-care delivery. Methods: The costs in 2019–20 were estimated for each type of care at allopathic urban primary health center (UPHC) and AYUSH facilities using top-down methodology and adding out-of-pocket expenditures (OOPE) incurred to reflect true costs. Data from national health survey, annual government budgets, and reports were used. Results: The average cost of an outpatient visit for allopathic care was ₹325 at a UPHC and ₹189 in a homeopathic dispensary and ₹692 in an Ayurvedic dispensary. While OOPE per visit at UPHC was ₹177, no OOPE was incurred at AYUSH facilities. The government expenditure per visit for allopathic care at UPHC at ₹148 was the lowest compared to any type of AYUSH care. The cost per facility for allopathic UPHC was higher than both Ayurvedic and homeopathic dispensaries. Unani dispensaries were least cost-effective, both in terms of cost per visit and cost per facility. Conclusion: Costs per visit at a facility are impacted by footfalls. For Ayurveda, despite lower facility costs as compared to UPHC, per visit costs were higher due to low utilization. Improving evidence-based utilization of AYUSH care is critical for the success of the government policy of mainstreaming AYUSH care at low cost.